Sub-micron/nano structure induced at polished silicon surface irradiated by single and double nanosecond laser pulses in distilled water. (8th April 2015) - Sobhani, M; Mahdieh, M H
Abstract: The polished side of the silicon target was irradiated by a train of single and double nanosecond laser pulses in distilled water. Under the conditions of our experiment, sub-micron/nano clusters are produced on the silicon surface by both single and double laser pulses. Electron micrographs of irradiated silicon were analyzed, from which the effective diameter and surface density of clusters was estimated. An in situ optical reflectivity measurement was performed to estimate the variation in the cluster heights. The results show that surface-cluster density and optical reflectivity are significantly affected by the number of laser pulses and the time separation between double laser pulses. Compared to single laser pulses, double laser pulses can affect more significantly the cluster heights and optical reflectivity.